1)-(m-3,8)+(4,8+m)+2m=
=-m+3,8+4,8+m+2m=
=8,6+2m
2)-2(2a-3b)+5(3a+4b)=
=-4a+6b+15a+20b=
=11a+26b
1) 2m+8.6; 2)11a+26b
Пошаговое объяснение:
1)-(m-3.8)+(4.8+m)+2m
-m+3.8+4.8+m+2m
сводим подобные
2m+8.6
2) -2(2a-3b)+5(3a+4b)
-4a+6b+15a+20b
11a+26b
1)-(m-3,8)+(4,8+m)+2m=
=-m+3,8+4,8+m+2m=
=8,6+2m
2)-2(2a-3b)+5(3a+4b)=
=-4a+6b+15a+20b=
=11a+26b
1) 2m+8.6; 2)11a+26b
Пошаговое объяснение:
1)-(m-3.8)+(4.8+m)+2m
-m+3.8+4.8+m+2m
сводим подобные
2m+8.6
2) -2(2a-3b)+5(3a+4b)
-4a+6b+15a+20b
сводим подобные
11a+26b